(untitled) (Journal of Fiber Bioengineering and Informatics, 2020)
As a common disease in the elderly, the research on knee arthritis is mostly clinical treatment, but the research on functional health care pants for the daily health care of knee osteoarthritis patients is less. In view of this phenomenon, this paper explores the function of the health pants through the interviews of experts and the questionnaire survey of patients, and analyzes the weight of the function demand. Aiming at the five functional requirements with large weight, the fabric was screened, tested and analyzed by grey correlation degree. According to the analysis results, choose the fabric with better function and choose different tissues according to different parts, so as to design a kind of health care pants for knee arthritis to meet the needs of health care and comfort.